Identification and Pathogenicity of Fusarium Species from Herbaceous Plants on Grassland in Qiaojia County, China - Yanzhu Gao; Zhixiao Zhang; Mei Ji; Sangzi Ze; Haodong Wang; Bin Yang; Lianrong Hu; Ning Zhao (Microorganisms)
The Fusarium species is an important plant pathogen that can cause plant diseases in grassland, leading to the degradation of grassland quality. However, the morphology of Fusarium is greatly affected by environmental factors, which makes it difficult to identify its species. In addition, the pathogenic ability of different Fusarium species in plants has not been fully studied. In this study, Fusarium isolates were obtained from grassland herbaceous plants via tissue separation. Through morphological means and based on ITS, RPB2, and TEF-1 gene sequences, we compared and constructed polygenic phylogenetic trees to classify and identify the Fusarium species. In addition, the pathogenicity of different Fusarium species was also analyzed. The results showed that a total of 24 Fusarium strains were successfully isolated from grassland, from which ten species were identified: F. flagelliforme, F. longifundum, F. clavum, F. scirpi, F. ipomoeae, F. oxysporum, etc. and were included in four complexes: Fusarium incarnatum-equiseti species complex (FIESC), Fusarium oxysporum species complex (FOSC), Fusarium tricinctum species complex (FTSC), and Fusarium sambucinum species complex (FSAMSC). Pathogenicity tests demonstrated that except for F. ipomoeae QJ5211, F. sambucinum QJ203, and F. acuminatum QJ1662, other Fusarium species had different degrees of pathogenic ability. This is the first study that discusses the effect of Fusarium on grassland disease control in this area. This study further provides clear pathogen information for the prevention and control of grassland diseases.